Activation of the Nucleus Taeniae of the Amygdala by Umami Taste in Domestic Chicks (Gallus gallus) - Protti-Sánchez, Francesca; Corrales Parada, Carlos Daniel; Mayer, Uwe; Rowland, Hannah M. (Frontiers in Physiology, 2022)
In chickens, the sense of taste plays an important role in detecting nutrients and choosing feed. The molecular mechanisms underlying the taste-sensing system of chickens is well studied, but the neural mechanisms underlying taste reactivity has received less attention. Here we report the short-term taste behaviour of chickens towards umami and bitter (quinine) taste solutions and the associated neural activity in the nucleus taeniae of the amygdala, nucleus accumbens and lateral septum. We found that chickens had more contact with and drank greater volumes of umami than bitter or a water control, and that chicks displayed increased head shaking in response to bitter compared to the other tastes. We found that there was a higher neural activity, measured as c-Fos activation, in response to umami taste in the right hemisphere of the nucleus taeniae of the amygdala. In the left hemisphere, there was a higher c-Fos activation of the nucleus taeniae of the amygdala in response to bitter than in the right hemisphere. Our findings provide clear evidence that chickens respond differently to umami and bitter tastes, that there is a lateralised response to tastes at the neural level, and reveals a new function of the avian nucleus taeniae of the amygdala as a region processing reward information.